Effects of co-digestion of cucumber residues to corn stover and pig manure ratio on methane production in solid state anaerobic digestion. (February 2018) - Wang, Yaya; Li, Guoxue; Chi, Menghao; Sun, Yanbo; Zhang, Jiaxing; Jiang, Shixu; Cui, Zongjun
Highlights: Cucumber residues was a good potential materiel for methane production. Co-digestion leads to increasing methane production compared to mono-feedstock. The highest methane yield feed was achieved with a 5:2:3 ratio of PM with CS and CR. Significant regularity of methane yields was obtained with different CR ratio. Regularity of methane production and microbial communities structure was obtained. Abstract: This study investigated the performance of co-digesting cucumber residues, corn stover, and pig manure at different ratios. Microbial community structure was analyzed to elucidate functional microorganism contributing to methane production during co-digestion. Results show that mixing cucumber residues with pig manure and corn stover could significantly improved methane yields 1.27–3.46 times higher than mono-feedstock. The methane yields decreased with the cucumber residues increasing when the pig manure ratio was fixed at 4 and 3, and was opposite at ratio 5. The optimal mixture ratio was T2 with the highest methane yield (305.4 mL/g VS) and co-digestion performance index (1.97). The main microbiological community in T2 was bacteria of Firmicutes (44.6%), Bacteroidetes (32.5%), Synergistetes (3.8%) and archaea of Methanosaeta (37.1%), Methanospirillum (18.2%). The mixture ratios changed the microbial community structures. The adding proportion of cucumber residues changed the community composition of the archaea, especially the proportion of Methanosaeta .